Degradation of cellulose and hemicelluloses by the brown rot fungus Piptoporus betulinus--production of extracellular enzymes and characterization of the major cellulases - Valášková, Vendula; Baldrian, Petr (Microbiology (Reading, England), 2006)
Piptoporus betulinus is a common wood-rotting fungus parasitic for birch (Betula species). It is able to cause fast mass loss of birch wood or other lignocellulose substrates. When grown on wheat straw, P. betulinus caused 65% loss of dry mass within 98 days, and it produced endo-1,4-beta-glucanase (EG), endo-1,4-beta-xylanase, endo-1,4-beta-mannanase, 1,4-beta-glucosidase (BG), 1,4-beta-xylosidase, 1,4-beta-mannosidase and cellobiohydrolase activities. The fungus was not able to efficiently degrade crystalline cellulose. The major glycosyl hydrolases, endoglucanase EG1 and beta-glucosidase BG1, were purified. EG1 was a protein of 62 kDa with a pI of 2.6-2.8. It cleaved cellulose internally, produced cellobiose and glucose from cellulose and cellooligosaccharides, and also showed beta-xylosidase and endoxylanase activities. The K(m) for carboxymethylcellulose was 3.5 g l(-1), with the highest activity at pH 3.5 and 70 degrees C. BG1 was a protein of 36 kDa with a pI around 2.6. It was able to produce glucose from cellobiose and cellooligosaccharides, but also produced galactose, mannose and xylose from the respective oligosaccharides and showed some cellobiohydrolase activity. The K(m) for p-nitrophenyl-1,4-beta-glucoside was 1.8 mM, with the highest activity at pH 4 and 60 degrees C, and the enzyme was competitively inhibited by glucose (K(i)=5.8 mM). The fungus produced mainly beta-glucosidase and beta-mannosidase activity in its fruit bodies, while higher activities of endoglucanase, endoxylanase and beta-xylosidase were found in fungus-colonized wood.
Keywords: beta-Mannosidase; Triticum; Kinetics; Fungal Proteins; Hydrogen-Ion Concentration; teplota; celulasy; Substrate Specificity; Cellulose 1,4-beta-Cellobiosidase; celobiosa; Carboxymethylcellulose Sodium; polysacharidy; Enzyme Inhibitors; Polyporales; xylosidasy; sodná sůl karboxymethylcelulosy; Isoelectric Point; Cellulases; Oligosaccharides; glukan-1,4-beta-glukosidasa; oligosacharidy; Temperature; celulosa-1,4-beta-cellobiosidasa; celulosa; molekulová hmotnost; Xylosidases; fungální proteiny; glukosa; inhibitory enzymů; Glucose; izoelektrický bod; Glucan 1,4-beta-Glucosidase; endo-1,4-beta-xylanasy; Endo-1,4-beta Xylanases; lignin; Enzyme Stability; Lignin; substrátová specifita; pšenice; Cellobiose; Molecular Weight; koncentrace vodíkových iontů; Cellulose; Polysaccharides; kinetika; stabilita enzymů; beta-mannosidasa